Wealth and its distribution in Germany, 1895-2021 - Thilo N. H. Albers; Charlotte Bartels; Moritz Schularick (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
German history over the past 125 years has been turbulent. Marked by two world wars, revolutions and major regime changes, as well as a hyperinflation and three currency reforms, expropriations and territorial divisions, it comprises extreme shocks to study the role of historical events, taxation, asset price changes, portfolio heterogeneity in affecting the wealth distribution in the long run. Combining tax and archival data, household surveys, historical national accounts, and rich lists, we document that the top 1% wealth share has fallen by half, from close to 50% in 1895 to 26% today. Nearly all of this decline was the result of changes that occurred between 1914 and 1952. Using a novel decomposition framework, we show that collapsing equity prices after World War I and in the Great Depression as well as taxation in the aftermath of World War II stand out as great equalizers in 20th century German history. After unification in 1990, two trends have left their mark on the German wealth distribution. Households at the top made substantial capital gains from rising business wealth while the middle-class had large capital gains in the housing market. The wealth share of the bottom 50% has halved since 1990. Our findings speak to the importance of historical shocks to the valuation of existing wealth and taxation in driving the evolution of the wealth distribution over the long run. In addition, our data revisions reveal that Germany's current wealth-income ratio is about 120 percentage points higher than previously thought.
Keywords: D31; E01; E21; H2; N3; 330; Wealth inequality; portfolio heterogeneity; saving; wealth taxation